Photon-assisted ultrafast electron-hole plasma expansion in direct band semiconductors - Troha, Tinkara; Klimovič, Filip; Ostatnický, Tomáš; Němec, Hynek; Kužel, Petr (Nanophotonics (Berlin, Germany), 2024)
Time-resolved terahertz spectroscopy is used to investigate formation and ultrafast long-distance propagation of electron-hole plasma in strongly photoexcited GaAs and InP. The observed phenomena involve fundamental interactions of electron-hole system with light, which manifest themselves in two different regimes: a coherent one with the plasma propagation speeds up to c/10 (in GaAs at 20 K) and an incoherent one reaching up to c/25 (in InP at 20 K), both over a macroscopic distance >100 μm. We explore a broad range of experimental conditions by investigating the two materials, by tuning their band gap with temperature and by controlling the interaction strength with the optical pump fluence. Our interpretation suggests that the observed phenomena should occur in most direct band semiconductors upon strong photoexcitation with low excess energy.
Keywords: semiconductors; terahertz spectroscopy; coherent light–matter interaction; electron–hole plasma expansion; Rabi dynamics; stimulated emission